Estimation of Millimeter Wave Attenuation Due to Rain using 2D Video Distrometer Data in Malaysia - Manhal Alhilali; Jafri Din; Michael Schönhuber; Hong Yin Lam (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The increasing use of millimeter wave frequency bands requires a good understanding of the atmospheric channel. In equatorial regions, rain plays the central role in the impairment of millimeter wave propagation. Using large amounts of precise data collected by a two-dimensional video distrometer in Malaysia, the rain-specific attenuation of both vertically and horizontally polarized waves at the 38 GHz frequency was computed by applying the T-matrix technique. Good agreement is observed between these computations and fitted power law models from neighboring areas, but the ITU-R Recommendation P.838-3 significantly underestimates the rain-specific attenuation. The importance of including raindrop axial ratio in the calculation is revealed by differences among the local fitted coefficients for the vertically polarized estimations. The power law fit is provided, and the measurement is verified.